QUALITY ASSESSMENT, SPECIFICS OF ORGANIZATION AND PROVISION OF MEDICAL CARE TO STROKE PATIENTS ACCORDING TO THE HOSPITAL REGISTER OF VRCPH NAMED AFTER ACADEMICIAN O. I. YUSHCHENKO OF VRC AND VCCH EMS FOR THE PERIOD 2017-2019 - Moskovko Serhiy Petrovych; Fiks Dmytro Oleksandrovych; Shayuk Alla Volodymyrivna; Cherkasova Lyubov Anatoliyivna (World Science, 2020)
Currently, one of the most important tasks is to improve the quality of medical services, which becomes possible in retrospective register analysis of medical and organizational technologies, which include algorithms for providing medical care, continuity of medical institutions, protocols for diagnosis and treatment of diseases. The stroke register was created on the basis of medical documentation of hospitals, which are the most typical for the Podillia region of Ukraine. Statistical processing of the results was performed using the licensed statistical package "Statistica 5.5" using parametric evaluation methods. Significant differences in the organization of the medical-diagnostic process and approaches to treatment have been established between the two medical institutions of Vinnytsia in the dynamics of time. There was a positive trend in the time of stroke treatment, the use of drugs with a high degree of evidence and the coverage of patients with specialized, multidisciplinary care in a stroke